Creative writing for publication: An action research study of motivation, engagement, and language development in Argentinian secondary schools - Banegas, Darío Luis; Lowe, Robert J. (Studies in Second Language Learning and Teaching, 2021)
There has been much research on the connections between second language (L2) writing and learner motivation. However, few studies have focused on contexts in which L2 learning is mandatory, rather than elective. This technical action research-based study evaluated a project in which teenage learners in Argentina were engaged in creative writing tasks, with the goal of including their final written pieces in a formal publication. Through focus group interviews and group discussions, it was found that the project had increased the motivation not only of the learners, but also of the teachers. Further, the study highlights the importance of making such writing tasks student-centered, and calls attention to the role played by the teachers in motivating and engaging students. The study suggests that effort should be made to develop more initiatives in formal education settings in order to motivate and engage learners involved in mandatory language study.